2005
DOI: 10.1177/154193120504901810
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics Evaluation of the Use of a Handled Shower-Cleaning Tool

Abstract: Cleaning a bathroom presents several risk factors for acute and cumulative musculoskeletal injury. This study attempted to determine if using a handled tool while cleaning a typical North American bathtub/shower combination reduces the stress placed on the musculoskeletal system when compared to the use of a spray cleaner and sponge. Nineteen right-handed female subjects cleaned a systematically dirtied shower/bathtub combination using a sponge and a handled tool 21 inches long. The subjects' rated their perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Third, task time differences due to the cleaning equipment used was not studied. However, Janowitz et al [ 20 ] found there to be no significant time difference between use of a sponge and a handled tool to clean a standard American shower/tub area. We expect that similar results would have been found in this study as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, task time differences due to the cleaning equipment used was not studied. However, Janowitz et al [ 20 ] found there to be no significant time difference between use of a sponge and a handled tool to clean a standard American shower/tub area. We expect that similar results would have been found in this study as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, worker interaction with the study cleaning tool resulted in lower subjective ratings of perceived effort during the study task. Janowitz et al [ 20 ] compared use of a handled tool to clean a bathtub/shower area with that of a sponge and spray cleaner. They found that trunk, wrist, and shoulder angles were significantly less deviated when using the handled tool.…”
Section: Introductionmentioning
confidence: 99%